Agenesis of the corpus callosum: A clinical approach to diagnosis. Issue 2 (27th May 2014) - Palmer, Elizabeth Emma; Mowat, David; Mirzaa, Ghayda M.; Paciorkowski, Alex R.
<x xml:space="preserve">Abstract</x> This review article aims to guide the clinician in establishing a diagnosis in patients with agenesis of the corpus callosum (ACC), presenting antenatally or postnatally. ACC may be isolated, or occur in association with other neuroanatomical lesions and/or congenital anomalies, and has many different genetic causes. Neuropsychological outcome varies considerably from normal to profound intellectual disability depending on the etiology. Approximately 25% of individuals with antenatally diagnosed apparently isolated ACC have intellectual disability. Subtle neurological, social, and learning deficits may still occur in those with normal intelligence and longitudinal neurocognitive follow‐up is recommended for all children with ACC. The finding of ACC should prompt detailed clinical assessment in order to determine and manage the underlying condition. It is recognized that genetic factors contribute to ACC in the vast majority of cases. Less commonly ACC can result from antenatal infections, vascular or toxic insults, and it is increasingly recognized that ACC, particularly isolated ACC, may be due to an interaction of a number of "modifier" genetic and environmental factors. There are a large number of genetic conditions in which ACC may be a feature. We suggest a diagnostic algorithm to help guide the clinician towards diagnosis, to provide outcome advice and to aid in genetic counseling. © 2014 Wiley Periodicals, Inc.